(untitled) - Brieger, Nick (New York, 1994)
The book is a breakthrough in business English materials. It gives a concise but thorough explanation of grammar and functions as well as plenty of practice exercises and tasks, all within ealistic business contexts.
Keywords: English language,English language,English language; Business english,Problems, exercises, etc,Grammar,Problems, exercises, etc,Textbooks for foreign speakers